Blackness in the Andes ethnographic vignettes of cultural politics in the time of multiculturalism - Rahier, Jean Muteba; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book examines, in Andean national contexts, the impacts of the'Latin American multicultural turn' of the past two decades on Afro Andean cultural politics, emphasizing both transformations and continuities.
Keywords: Social sciences; Ethnology -- Latin America; Latin America -- Politics and government; Anthropology; Ethnography; Sociology; Ethnicity; Social Sciences; Ethnicity Studies; Latin American Politics; Latin American Culture; Ethnography; Anthropology; Sociology, general